1 Answer | Add Yours
The most basic way is just to solve it. If we distribute and combine like terms on the left hand side, we get
`9(x-4)-7x=9x-9*4-7x=2x-36.` Distributing on the right hand side gives
`5(3x-2)=5*3x-5*2=15x-10,` so the whole equation simplifies to
`2x-36=15x-10.` If we subtract `2x` from both sides and add 10 to both sides, we get
`-26=13x,` and dividing both sides by 13 then gives `x=-2.`
Think about what we've really just done. We assumed that there is some number `x` that satisfies the equation and then performed basic arithmetic and algebraic operations to show that `x` can only be ```-2```, which means there is at most one solution. It's not hard to check that it is actually a solution, so we're done.
We’ve answered 315,453 questions. We can answer yours, too.Ask a question